Drought resistance of 2-year-old saplings of Mediterranean forest trees in the field: relations between water relations, hydraulics and productivity (Plant and soil, 2003)
Drought resistance was examined for 2-year-old saplings of Ceratonia siliqua L., Olea oleaster Hoffmgg. et Link., Quercus suber L. and Q. pubescens Willd. growing in the ﬁeld in Sicily, with the aim of testing their possible use in the reforestation of degraded areas. To this purpose, leaf conductance to water vapour (gL), transpiration rate (EL), relative water content (RWC) and water potential (L) were measured between pre-dawn and sunset, monthly from May to November. Parallel measurements of loss of hydraulic conductance of twigs of the current year (PLC) were made together with an estimate of whole-plant hydraulic conductance (KPLANT) on the basis of the ratio of maximum EL to (PD − MIN), where PD is pre-dawn L and MIN is the minimum diurnal L. C. siliqua saplings maintained high gL throughout the study period with high RWC (over 90%) and L. They grew rapidly and increased their foliage area (AL) by over 60% from May to winter rest. This was accompanied by low twig PLC (about 20% in September) resulting in high KPLANT all through the study period. In contrast, O. oleaster saplings underwent distinct dehydration in July, i.e. they showed stomatal closure due to a drop in RWC (to 75%) and L (to the turgor-loss point). This was apparently due to twig cavitation, resulting in a strong decrease of KPLANT. Plants, however, tolerated summer drought, and showed growth (AL increased by 15% from May to November). Saplings of Q. suber and Q. pubescens were much more vulnerable to twig cavitation (PLC was 35–48% from June to November) than the other two species, and their average KPLANT was lower. Saplings of Q. suber and Q. pubescens grew only during the wet spring period, and no new foliage was produced thereafter. Changes in twig hydraulic conductance played a dominant role in determining changes in KPLANT in that the two variables were well correlated to each other (r = 0.68 for P = 0.001). We conclude that C. siliqua is an ideal candidate for reforestation of Sicilian degraded areas as is O. oleaster that, however, requires some additional water supply in the summer, at least during the early years after plantation. In wetter locations of Sicily, to an altitude between 0 and 500 m, Q. suber and Q. pubescens can be used for reforestation with expected higher competitiveness of the latter over the former species.

Competitive strategies for water availability in two Mediterranean Quercus species (Plant, Cell & Environment, 1999)
Competition for water availability was studied in a mixed natural stand of Quercus suber L. and Quercus cerris L. growing in Sicily by measuring diurnal changes of leaf conductance to water vapour (gL), water potential (ΨL) and relative water content (RWC) in April, July and October 1997 as well as the seasonal changes in root hydraulic conductance per unit leaf surface area (KRL). Quercus cerris behaved as a drought-tolerant species, with strong reductions of KRL, ΨL, and RWC in the summer. By contrast, Q. suber appeared to withstand summer drought by an avoidance strategy based on reducing gL, maintaining ΨL and RWC high and KRL at the same level as that measured in the spring. A ‘conductance ratio’ (CR) was calculated in terms of the ratio of gL to KRL. Seasonal changes of this ratio contrasted in the two species, thus suggesting that Q. suber and Q. cerris did not really compete for available water. In the summer, when Q. suber was extracting water from the soil to maintain high leaf hydration, Q. cerris had restricted water absorption, thus suffering drought but tolerating its effects. The possibility that cohabitation of drought-tolerant with drought-avoiding species can be generalized is also discussed.

Seasonal changes of root hydraulic conductance (K RL) in four forest trees: an ecological interpretation (Plant Ecology, 1998)
This paper deals with the possibility of relating root hydraulic parameters to an ecological index describing the continentality/oceanicity of four forest trees. Root hydraulic conductance (KR) of seedlings of Fagus sylvatica L., Quercus ilex L., Quercus suber L. and Quercus pubescens Willd. was measured in May, August and November 1996. KR was calculated in terms of the relation of the water ﬂow through intact root systems in situ measured with the pressure chamber, and the pressure driving the ﬂow. The sufﬁciency of the root system to supply the foliage was estimated by dividing KR by the seedlings leaf surface area (AL) thus obtaining KRL. In the spring, KRL was largest in F. sylvatica and smallest in Q. pubescens with intermediate values recorded in Q. ilex and Q. suber. All the species studied showed a large decline in KRL just prior to the winter rest except for Q. suber which mantained KRL approximately constant through the period of study. In most cases, KRL changed in accordance with analogous changes in the ﬂow. When the total seedlings’ leaf surface area (AL) was plotted versus KRL, it appeared that KRL of Q. pubescens increased with AL, proportionally, while KRL of F. sylvatica was inversely related to AL. This, together with the largest KRL recorded in the summer in Q. pubescens, was interpreted as advantageous to this species (which is adapted to semi-arid environments) in that: (a) roots could supply water to foliage efﬁciently even during the adverse season and (b) the foliage growth could be sustained even in summer. No statistically signiﬁcant relation of KRL to the continentality index calculated for the four species studied on the basis of their European distribution, was found to exist. Nonetheless, our data appear to be encouraging for future research aimed at better interpreting the typical distribution areas of plant species.